In-service education and improvement of performance of nurses at a Hospital in Huanuco - Ortiz-Aguí, María Luz (2019)
Objective. To demonstrate the effectiveness of in-service education and improvement of performance of nurses  at a hospital in Huánuco, in 2018. Methods. The design was ex post facto, with 96 cases and 96 randomized controls. A survey and observation guide of performance were applied after ethical considerations, and   previously validated. In the inferential analysis, the Wilcoxon test was used with a p < 0.05. Results. In-service education was provided mostly by the Department of Nursing in a face-to-face form and within working hours, on the subject of the methodology of care, quality management, teamwork, occupational health, among others. 71.9 % (69) of the experimental group showed a performance at an efficient level, 17.7% (17) regular and 10.4 % (10) deficient. In the control group regular level performance prevailed with 54.2 % (52), followed by efficient level 30.2 % (29) and in 15.6 % (15) it was deficient. Conclusion. In-service education is effective in improving the performance of nurses, having contrasted significant differences [Z = -6,708; p = 0,000], the experimental group was more efficient than the control group